Pelatihan Keterampilan Mengolah Sampah Plastik di Yayasan Langkah Kecil Indonesia - Euis Widiati (Universitas Mathla'ul Anwar Banten, 2021)
PLASTIC WASTE PROCESSING SKILLS TRAINING AT THE INDONESIAN SMALL STEP FOUNDATION. Waste production is increasing every day in line with the increasing number of products and consumption patterns of society. What must be done to overcome this increase in waste volume is by reducing the volume of waste from its source through community empowerment. In fostering concern for the environment and improving the economy and society, it is necessary to provide skills in the form of handicrafts that are able to process waste into something that has added value and selling value. So that the activity program